Analisis Pengaruh Pengajaran dan Sertifikasi Guru terhadap Kompetensi Guru pada Sekolah Menengah Kejuruan Di Wilayah Parung Panjang Kabupaten Bogor - Akhmar Barsah; Aden Prawiro Sudarso; Denok Sunarsi (Mahesa Research Center, 2020)
This study aims to determine the effect of information technology-based teaching and teacher certification on teacher competence and its implications for teacher performance at Vocational High Schools in Parung Panjang, Bogor Regency, West Java. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, determination and hypothesis testing. The results of this research that information technology-based teaching has a significant effect on teacher competence by obtaining the hypothesis test t count> t table (3.978> 1.980). Teacher certification has a significant effect on teacher competence by obtaining the hypothesis test t count> t table (4.449> 1.980). Information technology-based teaching and teacher certification simultaneously have a significant effect on teacher competence by obtaining the hypothesis test F count> F table (19,213> 3,080). Information technology-based teaching has a significant effect on teacher performance by obtaining the hypothesis test t count> t table (3.030> 1.980). Teacher certification has a significant effect on teacher performance by obtaining the hypothesis test t count> t table (2.870> 1.980). Teacher competence has a significant effect on teacher performance by obtaining the hypothesis test t count> t table (3,747> 1,980). Information technology-based teaching, teacher certification and teacher competence simultaneously have a significant effect on teacher performance by obtaining the hypothesis test F count> F table (20,238> 2,680).